Electrode for non-aqueous electrolyte secondary battery
By employing PVDF and PVDF-HFP as binders in a specific mass ratio within the electrode active material layer of nonaqueous electrolyte secondary batteries, the batteries' output characteristics are improved, addressing the issue of insufficient capacity at high discharge rates.
Patent Information
- Application Number
- JP2021013307
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-29
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2041-01-29
AI Technical Summary
Nonaqueous electrolyte secondary batteries using the technology described in Patent Document 1 have insufficient output characteristics, particularly when discharged at a high discharge rate.
The use of polyvinylidene fluoride (PVDF) and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) as binders in the electrode active material layer, with a specific mass ratio of PVDF-HFP to electrode active material within the range of greater than 0 and less than 0.015, to improve output characteristics.
This configuration enhances the output characteristics of nonaqueous electrolyte secondary batteries, allowing for a larger capacity to be extracted when discharged at high rates.
Smart Images

Figure 0007662991000002 
Figure 0007662991000003 
Figure 0007662991000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode for a non-aqueous electrolyte secondary battery. [Background technology]
[0002] In recent years, the spread of various electric vehicles is expected to help solve environmental and energy problems. Secondary batteries have been developed as on-board power sources for driving motors, etc., which are key to the spread of these electric vehicles. As secondary batteries, non-aqueous electrolyte secondary batteries, which are expected to have high energy density and high output, have been attracting attention.
[0003] Here, Patent Document 1 discloses a technology aimed at improving the safety of non-aqueous electrolyte secondary batteries. Specifically, the technology described in Patent Document 1 is characterized in that a composite PTC binder containing polyvinylidene fluoride (PVDF) and a PTC (Positive Temperature Coefficient) function-imparting component is used as a binder for the electrode active material layer. As a result, when the temperature of the non-aqueous electrolyte secondary battery rises, the binder melts and the resistance of the electrode active material layer increases, thereby suppressing heat generation in the electrode active material layer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2018 / 128139 Summary of the Invention [Problem to be solved by the invention]
[0005] However, after investigations by the present inventors, it was found that a nonaqueous electrolyte secondary battery using the technology described in Patent Document 1 has a problem in that the output characteristics are insufficient (in particular, sufficient capacity cannot be extracted during discharge at a high discharge rate).
[0006] Therefore, an object of the present invention is to provide a means for improving the output characteristics of a non-aqueous electrolyte secondary battery. [Means for solving the problem]
[0007] The present inventors have conducted extensive research to solve the above problems. In the process, they have found that it is possible to improve the output characteristics of a non-aqueous electrolyte secondary battery by using polyvinylidene fluoride (PVDF) and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) as binders in an electrode active material layer and controlling the mass ratio of the PVDF-HFP to the electrode active material within a specific range, and have completed the present invention.
[0008] That is, according to one embodiment of the present invention, there is provided an electrode for a non-aqueous electrolyte secondary battery, comprising a current collector and an electrode active material layer disposed on a surface of the current collector. Here, the electrode active material layer comprises an electrode active material, a conductive assistant, and a binder, and the binder comprises polyvinylidene fluoride (PVDF) and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP). The mass ratio of the polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) to the electrode active material is greater than 0 and less than 0.015. Effect of the Invention
[0009] According to the present invention, it is possible to improve the output characteristics of a non-aqueous electrolyte secondary battery. [Brief description of the drawings]
[0010] [Figure 1] 1 is a cross-sectional view showing a schematic diagram of a stacked (flat) non-bipolar (internal parallel connection) secondary battery according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view illustrating a bipolar secondary battery according to another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, the above-mentioned embodiment of the present invention will be described with reference to the drawings, but the technical scope of the present invention should be determined based on the claims and is not limited to the following embodiments. The dimensional ratios in the drawings are exaggerated for the convenience of explanation and may differ from the actual ratios. In this specification, the range "X to Y" means "X or more and Y or less." Furthermore, unless otherwise specified, the operation and measurement of physical properties are performed under the conditions of room temperature (20 to 25°C) and relative humidity of 40 to 50% RH.
[0012] <Non-aqueous electrolyte secondary battery electrode> One embodiment of the present invention is an electrode for a non-aqueous electrolyte secondary battery (hereinafter, also simply referred to as "electrode") including a current collector and an electrode active material layer disposed on the surface of the current collector. Here, the electrode active material layer includes an electrode active material, a conductive assistant, and a binder, and the binder includes polyvinylidene fluoride (PVDF) and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP). The mass ratio of the polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) to the electrode active material is more than 0 and less than 0.015. The electrode for a non-aqueous electrolyte secondary battery of this embodiment can improve output characteristics.
[0013] FIG. 1 is a cross-sectional view that illustrates a flat (laminated) non-bipolar (internal parallel connection) secondary battery (hereinafter also simply referred to as a "laminated secondary battery") according to one embodiment of the present invention.
[0014] As shown in Fig. 1, the stacked secondary battery 10a of this embodiment has a structure in which a substantially rectangular power generating element 21, in which a charge / discharge reaction actually proceeds, is sealed inside a laminate film 29. Here, the power generating element 21 has a configuration in which a positive electrode in which a positive electrode active material layer 13 is arranged on both sides of a positive electrode collector 11', an electrolyte layer 17 made of a separator containing an electrolytic solution, and a negative electrode in which a negative electrode active material layer 15 is arranged on both sides of a negative electrode collector 12 are laminated. Specifically, the positive electrode, the electrolyte layer, and the negative electrode are laminated in this order such that one positive electrode active material layer 13 and the adjacent negative electrode active material layer 15 face each other with the electrolyte layer 17 interposed therebetween.
[0015] As a result, the positive electrode, the electrolyte layer, and the negative electrode constitute one unit cell layer 19. Therefore, the stacked secondary battery 10a shown in FIG. 1 can be said to have a configuration in which a plurality of unit cell layers 19 are stacked and electrically connected in parallel. The positive electrode current collectors of the outermost layers located on both outermost layers of the power generating element 21 each have the positive electrode active material layer 13 disposed on only one side, but active material layers may be provided on both sides. That is, instead of using a current collector dedicated to the outermost layer with an active material layer provided on only one side, a current collector having active material layers on both sides may be used as the current collector of the outermost layer as it is. Also, by reversing the arrangement of the positive electrode and the negative electrode from FIG. 1, the outermost negative electrode current collector may be located on both outermost layers of the power generating element 21, and the negative electrode active material layer may be disposed on one or both sides of the outermost negative electrode current collector.
[0016] A positive electrode current collector 25 and a negative electrode current collector 27 that are electrically connected to the electrodes (positive and negative electrodes) are attached to the positive electrode current collector 11' and the negative electrode current collector 12, respectively, and are structured to be sandwiched between the ends of the laminate film 29 and led out of the laminate film 29. The positive electrode current collector 25 and the negative electrode current collector 27 may be attached to the positive electrode current collector 11' and the negative electrode current collector 12 of the electrodes by ultrasonic welding, resistance welding, or the like, respectively, via a positive electrode terminal lead and a negative electrode terminal lead (not shown) as necessary.
[0017] Fig. 2 is a cross-sectional view showing a bipolar secondary battery according to another embodiment of the present invention. The bipolar secondary battery 10b shown in Fig. 2 has a structure in which a substantially rectangular power generating element 21, in which the charge / discharge reaction actually proceeds, is sealed inside a laminate film 29 that is a battery exterior body. In this specification, the bipolar lithium ion secondary battery may also be simply referred to as a "bipolar secondary battery," and an electrode for a bipolar lithium ion secondary battery may also be simply referred to as a "bipolar electrode."
[0018] As shown in FIG. 2, the power generating element 21 of the bipolar secondary battery 10b of this embodiment has a plurality of bipolar electrodes 23 in which a positive electrode active material layer 13 electrically coupled to one surface of a current collector 11 is formed, and a negative electrode active material layer 15 electrically coupled to the opposite surface of the current collector 11 is formed. The bipolar electrodes 23 are stacked with an electrolyte layer 17 interposed therebetween to form the power generating element 21. In this case, the bipolar electrodes 23 and the electrolyte layer 17 are alternately stacked so that the positive electrode active material layer 13 of one bipolar electrode 23 and the negative electrode active material layer 15 of the other bipolar electrode 23 adjacent to the one bipolar electrode 23 face each other with the electrolyte layer 17 interposed therebetween. That is, the electrolyte layer 17 is sandwiched and disposed between the positive electrode active material layer 13 of one bipolar electrode 23 and the negative electrode active material layer 15 of the other bipolar electrode 23 adjacent to the one bipolar electrode 23.
[0019] The adjacent positive electrode active material layer 13, electrolyte layer 17, and negative electrode active material layer 15 constitute one single cell layer 19. Therefore, it can be said that the bipolar secondary battery 10b has a configuration in which the single cell layers 19 are stacked. In addition, a seal part (insulating layer) 31 is arranged on the outer periphery of the single cell layer 19. This prevents liquid junctions due to leakage of the electrolyte from the electrolyte layer 17, prevents contact between adjacent current collectors 11 in the battery, and prevents short circuits caused by slight unevenness of the ends of the single cell layers 19 in the power generation element 21. The positive electrode active material layer 13 is formed on only one side of the outermost current collector 11a on the positive electrode side, which is located at the outermost layer of the power generation element 21. The negative electrode active material layer 15 is formed on only one side of the outermost current collector 11b on the negative electrode side, which is located at the outermost layer of the power generation element 21.
[0020] 2, a positive electrode current collector (positive electrode tab) 25 is disposed adjacent to the outermost current collector 11a on the positive electrode side, and extends out from the laminate film 29 that is the battery exterior body. Meanwhile, a negative electrode current collector (negative electrode tab) 27 is disposed adjacent to the outermost current collector 11b on the negative electrode side, and similarly extends out from the laminate film 29.
[0021] The number of times that unit cell layers 19 are stacked is adjusted according to the desired voltage. In bipolar secondary battery 10b, the number of times that unit cell layers 19 are stacked may be reduced if sufficient output can be ensured even if the thickness of the battery is made as thin as possible. In bipolar secondary battery 10b as well, it is preferable to have a structure in which power generating element 21 is vacuum-encapsulated in laminate film 29, which is the battery exterior body, and positive electrode current collector 25 and negative electrode current collector 27 are exposed to the outside of laminate film 29 in order to prevent external impacts and environmental deterioration during use.
[0022] Hereinafter, the main components of the electrode for a non-aqueous electrolyte secondary battery according to this embodiment will be described.
[0023] [Current collector] The current collector has a function of mediating the movement of electrons from the electrode active material layer. There are no particular limitations on the material constituting the current collector. For example, metals and conductive resins can be used as the material constituting the current collector.
[0024] Specifically, metals include aluminum, nickel, iron, stainless steel, titanium, and copper. In addition to these, a clad material of nickel and aluminum, a clad material of copper and aluminum, or a plated material of a combination of these metals can be preferably used. Also, a foil in which a metal surface is coated with aluminum, or a carbon-coated aluminum foil may be used. Among them, aluminum, stainless steel, copper, and nickel are preferred from the viewpoint of electronic conductivity and battery operating potential.
[0025] The latter resin having electrical conductivity may be a resin obtained by adding a conductive filler to a conductive polymer material or a non-conductive polymer material as required.
[0026] Examples of conductive polymer materials include polyaniline, polypyrrole, polythiophene, polyacetylene, polyparaphenylene, polyphenylenevinylene, polyacrylonitrile, polyoxadiazole, etc. Such conductive polymer materials have sufficient conductivity without the addition of a conductive filler, and are therefore advantageous in terms of facilitating the manufacturing process or reducing the weight of the current collector.
[0027] Examples of non-conductive polymeric materials include polyethylene (PE; high density polyethylene (HDPE), low density polyethylene (LDPE), etc.), polypropylene (PP), polyethylene terephthalate (PET), polyethernitrile (PEN), polyimide (PI), polyamideimide (PAI), polyamide (PA), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polymethyl acrylate (PMA), polymethyl methacrylate (PMMA), polyvinyl chloride (PVC), polyvinylidene fluoride (PVdF), polystyrene (PS), etc. Such non-conductive polymeric materials can have excellent electric potential resistance or solvent resistance.
[0028] A conductive filler may be added to the conductive polymer material or non-conductive polymer material as necessary. In particular, when the resin serving as the base material of the current collector is made of only a non-conductive polymer, a conductive filler is necessarily required to impart conductivity to the resin.
[0029] The conductive filler can be used without any particular limitation as long as it is a material having electrical conductivity. For example, metals and conductive carbons can be mentioned as materials having excellent electrical conductivity, potential resistance, or lithium ion blocking properties. The metal is not particularly limited, but preferably contains at least one metal selected from the group consisting of Ni, Ti, Al, Cu, Pt, Fe, Cr, Sn, Zn, In, and Sb, or an alloy or metal oxide containing these metals. The conductive carbon is also not particularly limited. Preferably, it contains at least one selected from the group consisting of acetylene black, Vulcan (registered trademark), Black Pearl (registered trademark), carbon nanofiber, Ketjen Black (registered trademark), carbon nanotube, carbon nanohorn, carbon nanoballoon, and fullerene.
[0030] The amount of conductive filler added is not particularly limited as long as it is an amount that can impart sufficient conductivity to the current collector, and is generally about 5 to 80 mass %.
[0031] The current collector may be a single layer structure made of a single material, or may be a laminate structure made of a suitable combination of layers made of these materials. From the viewpoint of reducing the weight of the current collector, it is preferable that the current collector includes at least a conductive resin layer made of a resin having electrical conductivity. In addition, from the viewpoint of blocking the movement of lithium ions between the single cell layers, a metal layer may be provided on a part of the current collector.
[0032] [Electrode active material layer] The electrode active material layer is disposed on the surface of the current collector and contains an electrode active material, a conductive assistant, and a binder. When the electrode according to the present embodiment is a positive electrode, the electrode active material is a positive electrode active material, and when the electrode according to the present embodiment is a negative electrode, the electrode active material is a negative electrode active material. In this specification, unless otherwise specified, matters common to positive and negative electrodes will be referred to as "electrode".
[0033] (Cathode active material) The positive electrode active material has a function of releasing ions such as lithium ions during charging and absorbing ions such as lithium ions during discharging.
[0034] Examples of the positive electrode active material include lithium-transition metal composite oxides such as LiMn2O4, LiCoO2, LiNiO2, Li(Ni-Mn-Co)O2, Li(Ni-Co-Al)O2, and those in which a part of these transition metals is replaced by other elements, lithium-transition metal phosphate compounds, and lithium-transition metal sulfate compounds. In some cases, two or more positive electrode active materials may be used in combination. Preferably, from the viewpoint of capacity and output characteristics, lithium-transition metal composite oxides are used as the positive electrode active material. More preferably, composite oxides containing lithium and nickel are used. More preferably, Li(Ni-Mn-Co)O2 and those in which a part of these transition metals is replaced by other elements (hereinafter also simply referred to as "NMC composite oxides"), or Li(Ni-Co-Al)O2 and those in which a part of these transition metals is replaced by other elements (hereinafter also simply referred to as "NCA composite oxides"), etc. are used. Particularly preferably, NMC composite oxides are used. NMC composite oxides and NCA composite oxides have a layered crystal structure in which lithium atomic layers and transition metal atomic layers are stacked alternately with oxygen atomic layers between them. Each atom of the transition metal M contains one Li atom, and the amount of Li that can be extracted is twice that of spinel-type lithium manganese oxides, meaning that the supply capacity is doubled, resulting in high capacity.
[0035] As described above, NMC composite oxides and NCA composite oxides also include composite oxides in which part of the transition metal element is substituted by other metal elements. Examples of such other elements include Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr, Fe, B, Ga, In, Si, Mo, Y, Sn, V, Cu, Ag, Zn, etc. Preferably, they are Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr, more preferably Ti, Zr, P, Al, Mg, Cr, and even more preferably Ti, Zr, Al, Mg, Cr from the perspective of improving cycle characteristics. However, other metal elements that can substitute the transition metal element of the NCA composite oxide are those other than Al.
[0036] Since the NMC composite oxide has a high theoretical discharge capacity, preferably, it has a composition represented by the general formula (1): Li a Ni b Mn c Co d M x O2 (wherein, in the formula, a, b, c, d, x satisfy 0.9 ≦ a ≦ 1.2, 0 < b < 1, 0 ≦ c ≦ 0.5, 0 < d ≦ 0.5, 0 ≦ x ≦ 0.3, and b + c + d + x = 1. M is at least one element selected from Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr). Here, a represents the atomic ratio of Li, b represents the atomic ratio of Ni, c represents the atomic ratio of Mn, d represents the atomic ratio of Co, and x represents the atomic ratio of M. From the perspective of cycle characteristics, in the general formula (1), it is preferably 0.4 ≦ b ≦ 0.6. The composition of each element can be measured, for example, by inductively coupled plasma (ICP) optical emission spectrometry.
[0037] Generally, nickel (Ni), cobalt (Co), and manganese (Mn) are known to contribute to capacity and output characteristics from the viewpoints of improving material purity and electron conductivity. Ti, etc. partially substitute transition metals in the crystal lattice. From the viewpoint of cycle characteristics, it is preferable that part of the transition element is substituted by other metal elements, and particularly preferably 0 < x ≦ 0.3 in the general formula (1). The crystal structure is stabilized by the solid solution of at least one selected from the group consisting of Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, and Cr. As a result, it is considered that a decrease in battery capacity can be prevented even when charge and discharge are repeated, and excellent cycle characteristics can be realized.
[0038] As a more preferable embodiment, in the general formula (1), it is preferable that b, c, and d are 0.44 ≦ b ≦ 0.51, 0.27 ≦ c ≦ 0.31, and 0.19 ≦ d ≦ 0.26 from the viewpoint of improving the balance between capacity and life characteristics. For example, LiNi 0.5 Mn 0.3 Co 0.2 O2 has a larger capacity per unit mass compared to LiCoO2, LiMn2O4, LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2, etc. which have proven track records in general consumer batteries. As a result, it has the advantage of being able to improve the energy density and fabricate a compact and high-capacity battery, and is thus also preferable from the viewpoint of cruising range.
[0039] Also, as a more preferable embodiment, from the viewpoint of having a larger capacity, LiNi 0.8 Co 0.1 Al 0.1 O2 and LiNi 0.8 Co 0.15 Al 0.05 O2 are preferable.
[0040] From the viewpoint of achieving high output, the average particle diameter of the positive electrode active material is preferably 1 to 100 μm, and more preferably 1 to 20 μm. In this specification, the average particle diameter of the particles is the Dian diameter (D50) measured by a particle size distribution measuring device using a laser diffraction / scattering method.
[0041] (Negative electrode active material) The negative electrode active material has a function of releasing ions such as lithium ions during discharge and absorbing ions such as lithium ions during charge.
[0042] Examples of the negative electrode active material include carbon materials such as graphite, soft carbon, and hard carbon, and lithium-transition metal composite oxides (e.g., Li4Ti5O 12 ), metal materials (tin, silicon), silicon-containing alloy-based negative electrode materials (e.g., Si 60 Sn 10 Ti 30 ), lithium alloy-based negative electrode materials (for example, lithium-tin alloy, lithium-silicon alloy, lithium-aluminum alloy, lithium-aluminum-manganese alloy, etc.). In some cases, two or more types of negative electrode active materials may be used in combination. From the viewpoint of capacity and output characteristics, silicon-containing alloy-based negative electrode materials, carbon materials, lithium-transition metal composite oxides, and lithium alloy-based negative electrode materials are preferably used as the negative electrode active materials. Of course, negative electrode active materials other than those mentioned above may be used.
[0043] The average particle size of the negative electrode active material is not particularly limited, but from the viewpoint of achieving high output, it is preferably 1 to 100 μm, more preferably 1 to 20 μm.
[0044] The content of the electrode active material in the electrode active material layer is, for example, 60% by mass or more and less than 100% by mass, preferably 80% by mass or more and 99.5% by mass or less, more preferably more than 95% by mass or more and 99.0% by mass or less, and even more preferably 97% by mass or more and 98.5% by mass or less, based on 100% by mass of the total solid content. If the content of the electrode active material is within the above range, both the battery capacity and the output characteristics can be achieved.
[0045] (Conductive assistant) The conductive assistant has a function of forming an electron conduction path (conductive passage) in the electrode active material layer. When such an electron conduction path is formed in the electrode active material layer, the internal resistance of the battery is reduced, and the output characteristics at high rates can be improved. In particular, it is preferable that at least a part of the conductive assistant forms a conductive passage that electrically connects the two main surfaces of the electrode active material layer (in this embodiment, a conductive passage that electrically connects from the first main surface in contact with the electrolyte layer side of the electrode active material layer to the second main surface in contact with the current collector side is formed). By having such a form, the electron transfer resistance in the thickness direction in the electrode active material layer is further reduced, so that the output characteristics at high rates of the battery can be further improved. Note that whether or not at least a part of the conductive assistant forms a conductive passage that electrically connects the two main surfaces of the electrode active material layer (in this embodiment, a conductive passage that electrically connects from the first main surface in contact with the electrolyte layer side of the electrode active material layer to the second main surface in contact with the current collector side is formed) can be confirmed by observing the cross section of the electrode active material layer using an SEM or an optical microscope.
[0046] Examples of the conductive assistant include particulate carbon materials and fibrous carbon materials. In this specification, particulate carbon materials refer to carbon materials with a primary particle aspect ratio of 20 or less. In this specification, fibrous carbon materials refer to carbon materials with an aspect ratio of 1000 or more. In this specification, the aspect ratios of particulate carbon materials and fibrous carbon materials respectively refer to the average value of the ratio of the major axis length to the minor axis length of 100 carbon materials randomly selected by a scanning electron microscope (SEM).
[0047] Examples of the particulate carbon material include carbon powders such as acetylene black, carbon black, channel black, thermal black, and Ketjen Black (registered trademark). Among them, acetylene black is preferred from the viewpoint of electrical conductivity. The average particle size (primary particle size) of the particulate carbon material (preferably acetylene black) is not particularly limited, but is preferably 10 to 500 nm, more preferably 10 to 100 nm, even more preferably 15 to 75 nm, and particularly preferably 20 to 60 nm. In addition, the aspect ratio (aspect ratio of primary particles) of the particulate carbon material (preferably acetylene black) is 20 or less as described above, but is preferably 10 or less, more preferably 5 or less, even more preferably 2 or less, and particularly preferably 1.5 or less (the lower limit is 1).
[0048] Examples of the fibrous carbon material include carbon nanotubes (single-walled carbon nanotubes and multi-walled carbon nanotubes), carbon nanofibers, vapor-grown carbon fibers, electrospun carbon fibers, polyacrylonitrile-based carbon fibers, and pitch-based carbon fibers. Among them, carbon nanotubes are preferred from the viewpoint of electrical conductivity. The diameter (minor axis) of the fibrous carbon material (preferably carbon nanotubes) is not particularly limited, but is preferably 1 to 100 nm, more preferably 2 to 50 nm, and even more preferably 5 to 20 nm. The length (major axis) of the fibrous carbon material (preferably carbon nanotubes) is not particularly limited, but is preferably 1 to 100 μm, more preferably 2 to 50 μm, and even more preferably 5 to 30 μm. In addition, the aspect ratio of the fibrous carbon material (preferably carbon nanotubes) is 1000 or more as described above, but is preferably 1500 or more, and more preferably 1800 or more. The upper limit of the aspect ratio of the fibrous carbon material (preferably carbon nanotubes) is not particularly limited, and may be, for example, 20,000 or less, 10,000 or less, 5,000 or less, or 4,000 or less.
[0049] In the electrode of this embodiment, it is preferable that the conductive assistant contains both the particulate carbon material and the fibrous carbon material as described above. That is, in a preferred embodiment of an electrode for a non-aqueous electrolyte secondary battery, the conductive assistant contains a particulate carbon material having an aspect ratio of 20 or less and a fibrous carbon material having an aspect ratio of 1000 or more. When the conductive assistant contains both the particulate carbon material and the fibrous carbon material, an electron conductive path is formed well. More specifically, the particulate carbon material is present near the surface of the electrode active material to form a short-distance electron conductive path, while the fibrous carbon material is dispersed in the electrode active material layer to form a medium- to long-distance electron conductive path. This allows an electron conductive path to be efficiently formed from the electrode active material to the current collector. As a result, in a non-aqueous electrolyte secondary battery having the electrode of this embodiment, the output characteristics can be further improved (especially, a larger capacity can be extracted during discharge at a high discharge rate). Furthermore, the amount of the conductive assistant in the electrode active material layer can be reduced by forming an electron conductive path well. As a result, it is possible to further improve the energy density of the non-aqueous electrolyte secondary battery.
[0050] From the viewpoint of better forming the above-mentioned electron conductive path, the mass ratio of the particulate carbon material to the fibrous carbon material (particulate carbon material:particulate carbon material) is preferably 1:10 to 1:1, more preferably 1:6 to 1:2, and even more preferably 1:5 to 1:3. When the mass ratio is within the above range, the electron conductive path is better formed, so that the output characteristics can be further improved (particularly, a larger capacity can be extracted during discharge at a high discharge rate). In addition, the energy density of the nonaqueous electrolyte secondary battery can be further improved.
[0051] The content of the conductive assistant contained in the electrode active material layer (the total amount of the particulate carbon material and the fibrous carbon material when included) is preferably 2% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less, based on 100% by mass of the total solid content of the electrode active material layer. At such an upper limit value, the aggregation of the conductive assistants is suppressed, and an electron conduction path is well formed, so that the output characteristics can be further improved (particularly, a larger capacity can be taken out during discharge at a high discharge rate). In addition, it is possible to further improve the energy density of the nonaqueous electrolyte secondary battery. The lower limit value of the content of the conductive assistant is not particularly limited, but is preferably more than 0% by mass, and is preferably 0.1% by mass or more, preferably 0.2% by mass or more, and more preferably 0.3% by mass or more. At such a lower limit value, there is a sufficient amount of conductive assistant to form an electron conduction path, so that the output characteristics can be further improved (particularly, a larger capacity can be taken out during discharge at a high discharge rate).
[0052] Needless to say, conductive assistants other than those mentioned above may be used as long as they do not impair the effects of the present invention.
[0053] (Binding agent) The binder has a function of maintaining the structure of the electrode active material layer by binding the members contained in the electrode active material layer to each other. The electrode according to this embodiment is characterized in that it contains polyvinylidene fluoride (PVDF) and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) as the binder, and the mass ratio of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) to the electrode active material is more than 0 and less than 0.015. By adopting such a configuration, the output characteristics can be improved in a non-aqueous electrolyte secondary battery having the electrode according to this embodiment (especially, a large capacity can be extracted during discharge at a high discharge rate). Although the detailed mechanism by which the above effect is achieved is unknown, the present inventors speculate as follows. The technical scope of the present invention is not limited to the following mechanism.
[0054] According to the study by the present inventors, it was found that the output characteristics are significantly improved by using PVDF and PVDF-HFP in combination, rather than using PVDF alone. This is believed to be because PVDF-HFP has a higher swelling property in an electrolyte than PVDF, and therefore the combination of PVDF and PVDF-HFP improves the ion conductivity of lithium ions and the like in the electrode active material layer. Furthermore, since PVDF-HFP has high flexibility, it is presumed that it penetrates into the gaps of other members (electrode active material, conductive assistant, etc.) contained in the electrode active material layer, improving the dispersibility of these. As a result, it is believed that an electron conduction path is well formed, and excellent output characteristics can be exhibited. In addition, the present inventors found that the above effect cannot be sufficiently obtained when the mass ratio of PVDF-HFP to the electrode active material is 0.015 or more. This is believed to be because the content of PVDF-HFP becomes too high, inhibiting the electron conduction path in the electrode active material layer.
[0055] In the electrode of this embodiment, PVDF is not particularly limited as long as it is a homopolymer of vinylidene fluoride. From the viewpoint of binding property, the molecular weight of PVDF is preferably 100,000 to 1,000,000, more preferably 300,000 to 800,000, and even more preferably 500,000 to 700,000.
[0056] In the electrode of this embodiment, PVDF-HFP is not particularly limited as long as it is a comonomer of vinylidene fluoride and hexafluoropropylene. The ratio of the hexafluoropropylene-derived structural unit contained in PVDF-HFP is preferably 6 mol% or more and 20 mol% or less, more preferably 6.5 mol% or more and 10 mol% or less, and particularly preferably 6.9 mol% or more and 8 mol% or less, based on the total structural units of PVDF-HFP. When the ratio of the hexafluoropropylene-derived structural unit is within the above range, the swelling property and flexibility in the electrolyte can be improved. As a result, the ionic conductivity and electronic conductivity in the electrode active material layer are improved, and excellent output characteristics can be exhibited (especially, a large capacity can be taken out during discharge at a high discharge rate).
[0057] In the electrode active material layer, the mass ratio of PVDF-HFP to the electrode active material is more than 0 and less than 0.015, preferably 0.002 to 0.009, more preferably 0.003 to 0.007, and particularly preferably 0.004 to 0.006. If the mass ratio is 0 (i.e., the electrode active material layer does not contain PVDF-HFP) or if the mass ratio is 0.015 or more, the effect of improving the output characteristics cannot be obtained as explained in the above mechanism.
[0058] In the electrode active material layer, the content of the binder is preferably less than 3 mass%, more preferably 2 mass% or less, even more preferably 1 mass% or less, even more preferably less than 1 mass%, particularly preferably 0.9 mass% or less, and most preferably 0.8 mass% or less, based on 100 mass% of the total solid content of the electrode active material layer. Since the binder does not directly contribute to the charge / discharge reaction, the energy density of the non-aqueous electrolyte secondary battery can be further improved by reducing the content as described above. The lower limit is not particularly limited as long as the structure of the electrode active material layer can be maintained, but is preferably 0.3 mass% or more, more preferably 0.5 mass% or more.
[0059] In the electrode active material layer, the mass ratio (PVDF:PVDF-HFP) of polyvinylidene fluoride (PVDF) to polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) is preferably 1:5 to 5:1, more preferably 1:4 to 4:1, even more preferably 1:2 to 2:1, particularly preferably 1:1.5 to 1.5:1, and most preferably 1:1.2 to 1.2:1. When the mass ratio is within the above range, even if the content of the binder in the electrode active material layer is relatively small (particularly, preferably 1 mass% or less, more preferably less than 1 mass%, even more preferably 0.9 mass% or less, particularly preferably 0.8 mass% or less), the binding property of PVDF is maintained, and a good balance with the effect of improving ionic conductivity and / or electronic conductivity of PVDF-HFP is obtained. On the other hand, when the content of the binder in the electrode active material layer is relatively high (particularly, preferably 1% by mass or more, more preferably more than 1% by mass, even more preferably 1.1% by mass or more, and particularly preferably 1.2% by mass or more), the mass ratio (PVDF:PVDF-HFP) is preferably 1:1.1 to 1:10, more preferably 1:1.5 to 1:6, and even more preferably 1:2 to 1:5. When the mass ratio is within the above range, the swelling property and flexibility in the electrolyte can be improved. As a result, the ionic conductivity and electronic conductivity in the electrode active material layer are improved, and excellent output characteristics can be exhibited (particularly, a large capacity can be taken out during discharge at a high discharge rate).
[0060] The electrode active material layer may contain a binder other than PVDF and PVDF-HFP (hereinafter, also referred to as "other binder"). However, from the viewpoint of further exerting the effects of the present invention, the content of the other binder in the electrode active material layer is preferably 10 mass% or less, more preferably 5 mass% or less, even more preferably 3 mass% or less, particularly preferably 1 mass% or less, and most preferably 0 mass% based on the total amount of the binder (i.e., the electrode active material layer does not contain other binder). The other binder is not particularly limited, and known materials can be appropriately adopted.
[0061] In the electrode for non-aqueous electrolyte secondary batteries of this embodiment, the thickness of the electrode active material layer is not particularly limited, and conventionally known knowledge about batteries can be appropriately referred to. For example, the thickness of the electrode active material layer is usually about 1 to 1000 μm, preferably 20 to 800 μm, more preferably 30 to 500 μm, and even more preferably 40 to 200 μm. The thicker the electrode active material layer is, the more electrode active material can be retained to exert sufficient capacity (energy density). On the other hand, the thinner the electrode active material layer is, the more the output characteristics can be improved (especially, a large capacity can be extracted during discharge at a high discharge rate).
[0062] (electrolyte) The electrode active material layer may further include an electrolyte solution. The electrolyte solution functions as a carrier for lithium ions. The electrolyte solution has a form in which a lithium salt is dissolved in a non-aqueous solvent.
[0063] Examples of non-aqueous solvents include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propionate (MP), methyl acetate (MA), methyl formate (MF), 4-methyldioxolane (4MeDOL), dioxolane (DOL), 2-methyltetrahydrofuran (2MeTHF), tetrahydrofuran (THF), dimethoxyethane (DME), propylene carbonate (PC), butylene carbonate (BC), dimethyl sulfoxide (DMSO), and γ-butyrolactone (GBL). Among these, from the viewpoint of further improving the rapid charging characteristics and output characteristics, the non-aqueous solvent is preferably a chain carbonate, more preferably at least one selected from the group consisting of diethyl carbonate (DEC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC), and more preferably selected from ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC).
[0064] Examples of the lithium salt include Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), Li(C2F5SO2)2N, LiPF6, LiBF4, LiClO4, LiAsF6, and LiCF3SO3. Among these, the lithium salt is preferably Li(FSO2)2N from the viewpoints of battery output and charge / discharge cycle characteristics.
[0065] The concentration of the lithium salt in the electrolyte is preferably 0.1 to 3.0 mol / L, and more preferably 0.8 to 2.2 mol / L.
[0066] The electrolyte may further contain additives other than the above-mentioned components. Specific examples of such compounds include ethylene carbonate, vinylene carbonate, methylvinylene carbonate, dimethylvinylene carbonate, phenylvinylene carbonate, diphenylvinylene carbonate, ethylvinylene carbonate, diethylvinylene carbonate, vinylethylene carbonate, 1,2-divinylethylene carbonate, 1-methyl-1-vinylethylene carbonate, 1-methyl-2-vinylethylene carbonate, 1-ethyl-1-vinylethylene carbonate, 1-ethyl-2-vinylethylene carbonate, and 1-ethyl-2-vinylethylene carbonate. Examples of the additives include ethylene carbonate, vinyl vinylene carbonate, allyl ethylene carbonate, vinyloxymethyl ethylene carbonate, allyloxymethyl ethylene carbonate, acryloxymethyl ethylene carbonate, methacryloxymethyl ethylene carbonate, ethynyl ethylene carbonate, propargyl ethylene carbonate, ethynyloxymethyl ethylene carbonate, propargyl oxyethylene carbonate, methylene ethylene carbonate, and 1,1-dimethyl-2-methylene ethylene carbonate. These additives may be used alone or in combination of two or more. The amount of additive used in the electrolyte solution may be appropriately adjusted.
[0067] [Method of manufacturing electrodes for non-aqueous electrolyte secondary batteries] The method for producing the electrode for the non-aqueous electrolyte secondary battery according to the present embodiment is not particularly limited, and a conventionally known method can be appropriately adopted. As an example, the electrode active material, the conductive assistant, and the binder are mixed together with a solvent to prepare an electrode slurry (positive electrode slurry, negative electrode slurry). Then, the electrode slurry is applied to the surface of a current collector, and the solvent is dried to form a coating film.
[0068] The solvent is not particularly limited, and N-methyl-2-pyrrolidone (NMP), dimethylformamide, dimethylacetamide, methylformamide, cyclohexane, hexane, water, and the like can be used.
[0069] The method for mixing the electrode active material, the conductive assistant, and the binder with the solvent is not particularly limited, but as shown in the examples described below, it is preferable to add the binder to the electrode active material and the conductive assistant dispersed in the solvent and mix them. More specifically, the electrode active material and the conductive assistant are kneaded and mixed with a solvent, and the binder is added to the mixture and mixed. By mixing in this order, the electrode active material, the conductive assistant, and the binder are sufficiently dispersed in the electrode slurry, and when the electrode active material layer is formed, an electron conduction path is well formed.
[0070] The concentration of the electrode slurry is not particularly limited. However, from the viewpoint of facilitating application of the electrode slurry described below, the concentration of the total solid content relative to 100% by mass of the electrode slurry is preferably 35 to 75% by mass, more preferably 40 to 70% by mass. When the concentration is within the above range, an electrode active material layer having a sufficient thickness can be easily formed by application.
[0071] The electrode slurry is then applied onto a current collector and dried. After application, pressing may be performed as necessary.
[0072] The method for applying the electrode slurry to the current collector is not particularly limited, and examples thereof include a screen printing method, a spray coating method, an electrostatic spray coating method, an inkjet method, and a doctor blade method.
[0073] The coating thickness of the electrode slurry (thickness before drying) is appropriately set in consideration of the thickness of the electrode active material layer to be formed. The coating thickness of the electrode slurry is preferably 200 to 2000 μm, and more preferably 400 to 1000 μm.
[0074] The drying method after applying the electrode active material slurry on the current collector is not particularly limited, and may be any method that removes at least a part of the solvent. The drying method may include heating. The drying conditions (drying time, drying temperature, etc.) may be appropriately set depending on the volatilization rate of the solvent contained in the applied electrode active material slurry, the application amount of the electrode active material slurry, etc.
[0075] When pressing is performed, the pressing means is not particularly limited, and for example, a calendar roll, a flat plate press, or the like can be used.
[0076] By the above steps, the electrodes (positive electrode, negative electrode) for the non-aqueous electrolyte secondary battery of this embodiment can be obtained.
[0077] <Nonaqueous electrolyte secondary battery> According to another embodiment of the present invention, a nonaqueous electrolyte secondary battery (hereinafter, also simply referred to as "secondary battery") having the above-mentioned electrode for nonaqueous electrolyte secondary battery is provided. The secondary battery has excellent output characteristics by including the above-mentioned electrode. In this embodiment, the positive electrode is the above-mentioned electrode, the negative electrode is the above-mentioned electrode, and the positive electrode and the negative electrode are the above-mentioned electrodes. Among them, the embodiment in which the positive electrode is the above-mentioned electrode is preferable. In addition, when the secondary battery of this embodiment includes an electrode other than the above-mentioned electrode, the electrode other than the above-mentioned electrode can be appropriately selected from conventionally known electrodes. Hereinafter, the main components other than the electrodes of the nonaqueous electrolyte secondary battery according to this embodiment will be described.
[0078] [Electrolyte layer] The electrolyte layer preferably has a configuration in which a separator is impregnated with an electrolytic solution (liquid electrolyte). The specific configuration and preferred embodiment of the electrolytic solution have been described above in the section (Electrolytic Solution), so detailed description will be omitted here. The electrolytic solution contained in the electrolyte layer may be the same as or different from the electrolytic solution contained in the electrode active material layer, but is preferably the same.
[0079] The separator constituting the electrolyte layer has a function of retaining the electrolyte to ensure lithium ion conductivity between the positive electrode and the negative electrode, and also a function of acting as a partition between the positive electrode and the negative electrode.
[0080] The separator may be in the form of, for example, a porous sheet separator made of a polymer or fiber capable of absorbing and retaining the electrolyte, or a nonwoven fabric separator.
[0081] As the separator of the porous sheet made of polymer or fiber, for example, a microporous (microporous membrane) can be used. Specific forms of the porous sheet made of the polymer or fiber include, for example, polyolefins such as polyethylene (PE) and polypropylene (PP); laminates of a plurality of these laminates (for example, a laminate having a three-layer structure of PP / PE / PP), polyimide, aramid, hydrocarbon resins such as polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), glass fibers, etc., and microporous (microporous membrane) separators can be mentioned.
[0082] The thickness of the microporous (microporous membrane) separator cannot be unequivocally defined because it varies depending on the application. For example, in applications such as motor-driven secondary batteries for electric vehicles (EVs), hybrid electric vehicles (HEVs), and fuel cell vehicles (FCVs), the thickness is preferably 4 to 60 μm for single or multi-layered structures. The micropore diameter of the microporous (microporous membrane) separator is preferably 1 μm or less at maximum (usually a pore diameter of about several tens of nm).
[0083] As the nonwoven fabric separator, conventionally known materials such as cotton, rayon, acetate, nylon, polyester, polyolefins such as PP and PE, polyimide, aramid, etc. are used alone or in combination. The bulk density of the nonwoven fabric is not particularly limited as long as sufficient battery characteristics can be obtained by the impregnated polymer gel electrolyte. The thickness of the nonwoven fabric separator is the same as that of the electrolyte layer, and is preferably 5 to 200 μm, and particularly preferably 10 to 100 μm.
[0084] In addition, the separator is preferably a separator in which a heat-resistant insulating layer is laminated on a porous substrate (separator with heat-resistant insulating layer). The heat-resistant insulating layer is a ceramic layer containing inorganic particles and a binder. The separator with heat-resistant insulating layer is one having high heat resistance, with a melting point or thermal softening point of 150°C or higher, preferably 200°C or higher. By having a heat-resistant insulating layer, the internal stress of the separator, which increases when the temperature rises, is alleviated, so that a heat shrinkage suppression effect can be obtained. As a result, it is possible to prevent the induction of short circuits between the electrodes of the battery, resulting in a battery configuration in which performance deterioration due to temperature rise is unlikely to occur. In addition, by having a heat-resistant insulating layer, the mechanical strength of the separator with heat-resistant insulating layer is improved, and the separator is unlikely to break. Furthermore, due to the heat shrinkage suppression effect and high mechanical strength, the separator is unlikely to curl during the battery manufacturing process.
[0085] The inorganic particles in the heat-resistant insulating layer contribute to the mechanical strength and thermal contraction suppression effect of the heat-resistant insulating layer. There are no particular limitations on the material used as the inorganic particles. Examples include oxides (SiO2, Al2O3, ZrO2, TiO2), hydroxides, and nitrides of silicon, aluminum, zirconium, and titanium, as well as composites thereof. These inorganic particles may be derived from mineral resources such as boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, and mica, or may be artificially produced. In addition, only one type of these inorganic particles may be used alone, or two or more types may be used in combination. Of these, from the viewpoint of cost, it is preferable to use silica (SiO2) or alumina (Al2O3), and it is more preferable to use alumina (Al2O3).
[0086] The weight of the heat-resistant particles is not particularly limited, but is preferably 5 to 15 g / m 2 Within this range, sufficient ion conductivity can be obtained, and this is preferable in terms of maintaining heat resistance.
[0087] The binder in the heat-resistant insulating layer serves to bond the inorganic particles together and between the inorganic particles and the resin porous substrate layer, ensuring stable formation of the heat-resistant insulating layer and preventing peeling between the porous substrate layer and the heat-resistant insulating layer.
[0088] The binder used in the heat-resistant insulating layer is not particularly limited, and for example, compounds such as carboxymethylcellulose (CMC), polyacrylonitrile, cellulose, ethylene-vinyl acetate copolymer, polyvinyl chloride, styrene-butadiene rubber (SBR), isoprene rubber, butadiene rubber, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl fluoride (PVF), and methyl acrylate can be used as the binder. Among these, it is preferable to use carboxymethylcellulose (CMC), methyl acrylate, or polyvinylidene fluoride (PVDF). These compounds may be used alone or in combination of two or more.
[0089] The binder content in the heat-resistant insulating layer is preferably 2 to 20% by mass relative to 100% by mass of the heat-resistant insulating layer. When the binder content is 2% by mass or more, the peel strength between the heat-resistant insulating layer and the porous substrate layer can be increased, and the vibration resistance of the separator can be improved. On the other hand, when the binder content is 20% by mass or less, the gaps between the inorganic particles are appropriately maintained, and sufficient lithium ion conductivity can be ensured.
[0090] The heat shrinkage rate of the separator with heat-resistant insulation layer is 2gf / cm at 150℃. 2 It is preferable that both MD and TD are 10% or less after 1 hour of storage under these conditions. By using such a highly heat-resistant material, it is possible to effectively prevent the separator from shrinking even if the heat generation increases and the internal temperature of the battery reaches 150°C. As a result, it is possible to prevent the induction of short circuits between the battery electrodes, resulting in a battery configuration that is less susceptible to performance degradation due to temperature rise.
[0091] [Positive and negative current collectors] The material constituting the current collector plates (25, 27) is not particularly limited, and any known highly conductive material conventionally used as a current collector plate for a lithium ion secondary battery may be used. As the material constituting the current collector plates, for example, metal materials such as aluminum, copper, titanium, nickel, stainless steel (SUS), and alloys thereof are preferable. From the viewpoints of light weight, corrosion resistance, and high conductivity, aluminum and copper are more preferable, and aluminum is particularly preferable. The positive electrode current collector plate 25 and the negative electrode current collector plate 27 may be made of the same material or different materials.
[0092] [Positive and negative leads] Although not shown in the figures, the current collector 11 and the current collector plates (25, 27) may be electrically connected via a positive electrode lead and a negative electrode lead. As the constituent materials of the positive electrode and the negative electrode lead, materials used in known lithium ion secondary batteries may be similarly adopted. Note that the part removed from the exterior body is preferably covered with a heat-resistant insulating heat shrink tube or the like so as not to come into contact with peripheral devices or wiring, causing a current leak and affecting products (e.g., automobile parts, particularly electronic devices, etc.).
[0093] [Sealing part] The sealing portion (insulating layer) 31 is a member specific to bipolar secondary batteries (series stacked batteries) and has a function of preventing leakage of electrolyte from the electrolyte layer. The sealing portion 31 also has a function of preventing contact between current collectors and short circuit at the end of the unit cell layer. The material constituting the sealing portion may be any material that has insulation properties, sealing properties against the falling off of solid electrolyte, sealing properties against moisture permeation from the outside (sealing properties), heat resistance under the battery operating temperature, and the like. For example, acrylic resin, urethane resin, epoxy resin, polyethylene resin, polypropylene resin, polyimide resin, rubber (ethylene-propylene-diene rubber: EPDM), and the like may be used. Also, isocyanate-based adhesives, acrylic resin-based adhesives, cyanoacrylate-based adhesives, and the like may be used, and hot melt adhesives (urethane resin, polyamide resin, polyolefin resin), and the like may be used. Among these, from the viewpoints of corrosion resistance, chemical resistance, ease of production (film-forming ability), cost-effectiveness, etc., polyethylene resin and polypropylene resin are preferably used as the constituent material of the sealing part, and it is more preferable to use a resin copolymerized with ethylene, propylene, and butene, with amorphous polypropylene resin as the main component.
[0094] [Battery exterior] As the battery exterior body, a known metal can case can be used, and a bag-shaped case using a laminate film 29 containing aluminum that can cover the power generating element as shown in Figs. 1 and 2 can be used. The laminate film can be, for example, a three-layer laminate film formed by laminating PP, aluminum, and nylon in this order, but is not limited thereto. A laminate film is preferable from the viewpoint of being excellent in high output and cooling performance and being suitable for use in batteries for large equipment such as EVs and HEVs. In addition, an aluminate laminate is more preferable as the exterior body because the group pressure applied to the power generating element from the outside can be easily adjusted and the thickness of the electrolyte layer can be easily adjusted to the desired thickness.
[0095] The nonaqueous electrolyte secondary battery according to the present embodiment can exhibit excellent output characteristics, and is therefore suitable for use as a power source for driving EVs and HEVs.
[0096] [Battery pack] A battery pack is made up of multiple batteries connected together. More specifically, it is made up of at least two batteries connected in series or parallel or both. By connecting them in series or parallel, it is possible to freely adjust the capacity and voltage.
[0097] A small, removable assembled battery can be formed by connecting a plurality of batteries in series or in parallel. Then, a large capacity, high output assembled battery (battery module, battery pack, etc.) suitable for a vehicle driving power source or an auxiliary power source that requires a high volumetric energy density and a high volumetric output density can be formed by further connecting a plurality of such small, removable assembled batteries in series or in parallel. How many batteries are connected to form an assembled battery, and how many stages of small assembled batteries are stacked to form a large capacity assembled battery can be determined according to the battery capacity and output of the vehicle (electric vehicle) in which the battery is to be installed.
[0098] [vehicle] The nonaqueous electrolyte secondary battery of this embodiment has excellent output characteristics (especially, sufficient capacity can be obtained when discharging at a high discharge rate). Furthermore, the volumetric energy density is high. In vehicle applications such as electric vehicles, hybrid electric vehicles, fuel cell vehicles, and hybrid fuel cell vehicles, higher capacity and larger current are required compared to electric and portable electronic device applications. Therefore, the nonaqueous electrolyte secondary battery can be suitably used as a power source for vehicles, for example, a power source for driving a vehicle or an auxiliary power source.
[0099] Specifically, a battery or a battery pack formed by combining a plurality of batteries can be mounted on a vehicle. In the present invention, a battery with a large capacity and excellent output characteristics can be configured, and thus mounting such a battery on a vehicle can configure a plug-in hybrid electric vehicle with a long EV driving distance or an electric vehicle with a long driving distance per charge. Examples of vehicles include hybrid cars, fuel cell cars, and electric cars (all of which include four-wheeled vehicles (commercial vehicles such as passenger cars, trucks, and buses, and light cars, etc.), as well as two-wheeled vehicles (motorcycles) and three-wheeled vehicles). However, the application is not limited to automobiles, and the battery can be applied to various power sources of other vehicles, such as moving bodies such as trains, and can also be used as a mounted power source for uninterruptible power supplies and the like. EXAMPLES
[0100] The present invention will be explained in more detail below using examples and comparative examples, but it is not limited to the following examples in any way.
[0101] [Production Example] <Preparation of negative electrode> A solid content consisting of 95.5 mass% graphite (average particle size: 20 μm) as the negative electrode active material, 0.5 mass% carbon black as the conductive assistant, and 4 mass% PVDF as the binder was prepared. An appropriate amount of N-methyl-2-pyrrolidone (NMP) was added to this solid content, and the mixture was mixed at 2000 rpm for 6 minutes using a planetary stirring type mixing and kneading device "Awatori Rentaro" (ARE-310, manufactured by Thinky Corporation) to prepare a negative electrode slurry. The negative electrode slurry was uniformly applied to Cu foil placed on a smooth plate using a doctor blade so that the thickness of the negative electrode active material layer was 86 μm. The mixture was then dried for 2 hours on a hot plate heated to 80 ° C to prepare a negative electrode.
[0102] [Example 1] <Preparation of positive electrode> Positive electrode active material LiNi 0.8 Mn 0.1 Co 0.1A solid content consisting of 98.5% by mass of O2 (abbreviation: NMC811, average particle size: 10 μm), 0.4% by mass of carbon nanotubes (abbreviation: CNT, fiber diameter: 10 nm, fiber length: 20 μm, aspect ratio: 2000) as a conductive assistant, 0.1% by mass of acetylene black (abbreviation: AB, HS-100, manufactured by Denka, average primary particle size: 48 nm, aspect ratio: 1) as a conductive assistant, 0.8% by mass of PVDF (Kureha KF Polymer W # 7200, manufactured by Kureha) as a binder, and 0.2% by mass of PVDF-HFP (Kyner Flex 2501-10, manufactured by Arkema, proportion of hexafluoropropylene-derived structural units 6.9 mol%) as a binder was prepared. First, the positive electrode active material (total amount) and the conductive assistant (total amount of carbon nanotubes and acetylene black) were kneaded. N-methyl-2-pyrrolidone (NMP) was added to the mixture so that the solid content concentration was 85%, and the mixture was mixed for 5 minutes at 2000 rpm using a planetary stirring type mixing and kneading device "Awatori Rentaro" (ARE-310, manufactured by Thinky Corporation). N-methyl-2-pyrrolidone (NMP) was added to the mixture so that the solid content concentration was 80%, and the mixture was mixed for 5 minutes at 2000 rpm using the above-mentioned mixing and kneading device. A binder (total amount of PVDF and PVDF-HFP) was added to the mixture, and the mixture was mixed for 2 minutes at 2000 rpm using the above-mentioned mixing and kneading device. N-methyl-2-pyrrolidone (NMP) was added to the mixture so that the solid content concentration was 70%, and the viscosity was adjusted to prepare a positive electrode slurry. The positive electrode slurry was uniformly applied to an Al foil placed on a smooth plate using a doctor blade so that the thickness of the positive electrode active material layer was 62 μm. Thereafter, the resultant was dried on a hot plate heated to 80° C. for 30 minutes, and then transferred to a vacuum dryer where it was dried under vacuum at 130° C. for 8 hours to prepare a positive electrode.
[0103] <Making a lithium-ion battery> The obtained positive electrode was placed on a 12 cm 2 , negative electrode 13cm 2The laminate was cut so that it was. For the positive electrode, an aluminum foil with an Al terminal was laminated on the current collector foil side of the cut positive electrode. For the negative electrode, a copper foil with an Ni terminal was laminated on the current collector foil side of the cut negative electrode. A separator (manufactured by Celgard, made of PP) was inserted on the electrode active material layer side of the positive electrode and negative electrode to form a laminate. This laminate was sandwiched between heat-sealed aluminum laminate films, and a non-aqueous electrolyte obtained by dissolving Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI) 2mol / L in a mixed solvent of ethylene carbonate (EC) ethyl methyl carbonate (EMC) (volume ratio 3:7 (EC:EMC)) as a non-aqueous solvent was injected, and then vacuum sealed. In this way, a pouch-type lithium ion battery was produced in which the positive electrode and the negative electrode were laminated so as to face each other through the separator.
[0104] [Example 2] A lithium ion battery was produced in the same manner as in Example 1, except that in the preparation of the positive electrode, the proportion of PVDF was changed to 0.5 mass % and the proportion of PVDF-HFP was changed to 0.5 mass %.
[0105] [Example 3] A lithium ion battery was produced in the same manner as in Example 1, except that in the preparation of the positive electrode, the proportion of PVDF was changed to 0.2 mass % and the proportion of PVDF-HFP was changed to 0.8 mass %.
[0106] [Comparative Example 1] A lithium ion battery was produced in the same manner as in Example 1, except that in the preparation of the positive electrode, the proportion of carbon nanotubes was changed to 0.5 mass%, the proportion of acetylene black to 0 mass%, the proportion of PVDF to 1 mass%, and the proportion of PVDF-HFP to 0 mass%.
[0107] [Comparative Example 2] A lithium ion battery was produced in the same manner as in Example 1, except that in the preparation of the positive electrode, the proportion of PVDF was changed to 1 mass % and the proportion of PVDF-HFP was changed to 0 mass %.
[0108] [Comparative Example 3] In the preparation of the positive electrode, LiNi 0.8Mn 0.1 Co 0.1 A lithium ion battery was produced in the same manner as in Example 1, except that the ratio of O2 was changed to 96.5 mass %, the ratio of PVDF was changed to 1.5 mass %, and the ratio of PVDF-HFP was changed to 1.5 mass %.
[0109] [Output characteristic evaluation] The output characteristic evaluation was carried out by placing the lithium ion secondary batteries prepared in Examples 1 to 3 and Comparative Examples 1 to 3 in a thermostatic chamber (ARSF-0250-10, manufactured by Espec Corporation) set at 45°C. The lithium ion secondary battery prepared above was sandwiched between a 5 mm thick urethane rubber and a silicone sponge sheet, and was evaluated in a state where it was restrained at six points using a 10 mm thick metal plate and M6 screws. First, to confirm the capacity at a low rate, charging and discharging were performed twice at a cell voltage range of 2.5 to 4.3 V and a current value of 0.1 C rate. The capacity obtained at the 2.5 V cutoff during the first discharge was taken as the reference capacity of the cell. Next, charging and discharging were performed by increasing the discharge rate stepwise to 0.5 C, 1 C, and 2 C while keeping the charge rate fixed at 0.1 C. Then, the capacity obtained under the cell voltage 2.5 V cutoff condition when discharging at a 2 C rate was taken as the effective capacity. The 2C / 0.1C discharge capacity retention rate (%) was calculated by dividing the 2C effective capacity obtained based on these values by the 0.1C reference capacity × 100. The results are shown in Table 1.
[0110] [Table 1]
[0111] The above results show that the lithium ion battery using the positive electrode according to the present invention has improved output characteristics compared to the comparative battery. [Explanation of symbols]
[0112] 10a laminated secondary battery, 10b Bipolar secondary battery; 11 current collector, 11a: outermost current collector on the positive electrode side; 11b: an outermost current collector on the negative electrode side; 11' Positive electrode current collector 12 Negative electrode current collector 13 positive electrode active material layer, 15 negative electrode active material layer, 17 electrolyte layer, 19 cell layer, 21 Power generation elements, 23 Bipolar electrodes, 25 Positive current collector (positive tab), 27 negative electrode current collector (negative electrode tab), 29 Laminating film, 31 Sealing part.
Claims
1. An electrode for a non-aqueous electrolyte secondary battery comprising a current collector and an electrode active material layer disposed on a surface of the current collector, The electrode active material layer contains an electrode active material, a conductive assistant, and a binder, The binder includes polyvinylidene fluoride (PVDF) and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP); An electrode for a non-aqueous electrolyte secondary battery, in which a mass ratio of the polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) to the electrode active material is greater than 0 and not more than 0.009, and a mass ratio of the polyvinylidene fluoride (PVDF) to the polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) (PVDF:PVDF-HFP) is 1:5 to 5:1 (excluding those in which the binder contains a first polymer binder containing polyvinylidene fluoride and a second polymer binder containing a copolymer of chlorotrifluoroethylene and polyvinylidene fluoride, a copolymer of hexafluoropropylene and polyvinylidene fluoride, or a mixture thereof, and the second polymer binder is contained in an amount of 20 to 80 parts by mass per 100 parts by weight of the first polymer binder).
2. An electrode for a non-aqueous electrolyte secondary battery comprising a current collector and an electrode active material layer disposed on a surface of the current collector, The electrode active material layer contains an electrode active material, a conductive assistant, and a binder, the binder contains only polyvinylidene fluoride (PVDF) and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP); A mass ratio of the polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) to the electrode active material is greater than 0 and not greater than 0.009, and a mass ratio of the polyvinylidene fluoride (PVDF) to the polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) (PVDF:PVDF-HFP) is 1:5 to 5:1 (excluding those in which the mass ratio (PVDF:PVDF-HFP) is 100:20 to 100:80).
3. The polyvinylidene fluoride-hexafluoropropylene (P 3. The electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein a mass ratio of VDF to HFP is 0.002 or more and 0.009 or less.
4. 4. The electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the content of the binder is less than 3% by mass with respect to 100% by mass of the total solid content of the electrode active material layer.
5. 5. The electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein a mass ratio (PVDF:PVDF-HFP) of the polyvinylidene fluoride (PVDF) to the polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) is 1:4 to 4:
1.
6. 6. The electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the conductive assistant comprises a particulate carbon material having an aspect ratio of 20 or less and a fibrous carbon material having an aspect ratio of 1000 or more.
7. 7. The electrode for a nonaqueous electrolyte secondary battery according to claim 6, wherein a mass ratio of the carbon material particles to the carbon material fibers (carbon material particles:carbon material fibers) is 1:10 to 1:
1.
8. 8. The electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the content of the conductive assistant is 0.5% by mass or less, relative to 100% by mass of the total solid content of the electrode active material layer.
9. A non-aqueous electrolyte secondary battery comprising the electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 8.
Citation Information
Patent Citations
Polymer electrolyte cell
JP2002050405A
Lithium secondary battery, power storage device including lithium secondary battery, and method for manufacturing lithium secondary battery
JP2016131123A
Electrode and electrochemical device including the same
KR1020170045910A
Non-aqueous electrolyte secondary battery and material for use in same
WO2018128139A1